Silencing of selected glutamate receptor subunits modulates cancer growth - Luksch, Hella; Uckermann, Ortrud; Stepulak, Andrzej; Hendruschk, Sandy; Marzahn, Jenny; Bastian, Susanne; Staufner, Christian; Temme, Achim; Ikonomidou, Chrysanthy (Anticancer research, 2011)
Background: Emerging evidence supports a role for glutamate in the biology of cancer. We studied the impact of glutamate receptor subunit silencing on cancer phenotype. Materials and Methods: Different fragments of the coding region for ionotropic glutamate receptor AMPA 4 (GLUR4), ionotropic glutamate receptor N-methyl D-aspartate 1 (NR1), ionotropic glutamate receptor kainate 5 (KA2) and ionotropic glutamate receptor N-methyl D-aspartate 2D (NR2D) were stably transfected into human TE671, RPMI8226 and A549 cell lines. Resulting changes in cell proliferation, migration and mRNA expression of genes that determine cancer phenotype were assayed. Results: Decreased expression of GLUR4 markedly increased cancer cell proliferation, whereas decreased expression of NR1 markedly reduced the propensity of cancer cells to proliferate. Knockdown of KA2 and NR2D did not influence cancer phenotype. Gene silencing of GLUR4 modulated the mRNA expression of various genes in these cancer cell lines, as determined with the Human Cancer PathwayFinder™ PCR Array. Knockdown of GLUR4 influenced the expression and function of genes involved in invasion and metastasis, tumour suppressor genes, oncogenes and adhesion genes. Conclusion: The findings suggest that glutamate receptor subunits on cancer cells are linked to biochemical pathways that regulate malignant phenotype.